Archiwum Herminy von Reuss: korespondencja rodzin Reuss, Schönaich-Carolath, Hohenzollern oraz Prittwitz und Gaffron w zbiorach WiMBP im. C. Norwida w Zielonej Górze = The Hermina von Reuss Archive: correspondence of the Reuss, Schönaich-Carolath, Hohenzollern, and Prittwitz und Gaffron families in the collections of the C. Norwid Provincial and Municipal Public Library in Zielona Góra - Kuczer, Jarosław (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The materials stored at the Provincial and Municipal Public Library in Zielona Góra under the name "Hermina von Reuss Archive" constitute part of the von Schönaich-Carolath family archive, which was dispersed after 1945, and the personal archive of Hermina von Reuss. Discovered in 1971 by Grzegorz Chmielewski, then director of the library, they were subsequently purchased from a private owner and secured in the institution's warehouses. The first attempts at systematization were conducted in the 1970s by Jan Sczaniecki, a historian and employee of the WiMBP in Zielona Góra. However, because these efforts left the entire material without a clearly defined chronological axis, with only a partially clarified thematic division, a decision was made to comprehensively reorganize the collection's storage, so that it could then be made available in a readable form to those interested in the subject. The holdings of the "Hermina von Reuss Archive" in Zielona Góra primarily consist of correspondence from families currently associated with its owner: the Schönaichs, Hohenzollerns, and Prittwitz und Gaffrons, dating from the late 19th century to the end of World War II. The collection comprises letters and various materials: press, interviews, photographs, etc., collected in the Partition over a century. The family archive once had a much longer provenance and content, but the events of 1944-1945 and the plunder of German noble estates in Silesia led to the destruction or loss of most of these collections. The archive primarily housed documents and copies of the family records of the Counts von Schönaich and Princes von Carolath. They took over the Zabór estate in 1783, along with all the materials collected there from the time when it was owned by the Tschammer, Dünnewald, and Cosel families. Parts of the preserved material are now stored at the State Archives in Zielona Góra.
Keywords: Zabór; Hermine von Reuss-Hohenzollern (1887-1947); archiwa prywatne; korespondencja; zbiory biblioteczne; Wojewódzka i Miejska Biblioteka Publiczna im. Cypriana Norwida (Zielona Góra); private archives; library collections; correspondence